2011
DOI: 10.1242/jcs.091140
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 activation in heart is controlled by melusin, focal adhesion kinase and the scaffold protein IQGAP1

Abstract: SummaryExtracellular signal-regulated kinase 1/2 (ERK1/2) signalling is a key pathway in cardiomyocyte hypertrophy and survival in response to many different stress stimuli. We have previously characterized melusin as a muscle-specific chaperone protein capable of ERK1/2 signalling activation in the heart. Here, we show that in the heart, melusin forms a supramolecular complex with the proto-oncogene c-Raf, MEK1/2 (also known as MAPKK1/2) and ERK1/2 and that melusin-bound mitogen-activated protein kinases (MAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 29 publications
0
66
0
Order By: Relevance
“…In addition, Melusin also organizes a signalosome complex regulating the ERK1/2 pathway [20]. We have shown, in fact, that melusin interacts with c-Raf, MEK1/2 and ERK1/2 MAP Kinases, as well as with their scaffold molecule IQGAP-1 [55]. An additional key element also present in the complex is the focal adhesion kinase FAK.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…In addition, Melusin also organizes a signalosome complex regulating the ERK1/2 pathway [20]. We have shown, in fact, that melusin interacts with c-Raf, MEK1/2 and ERK1/2 MAP Kinases, as well as with their scaffold molecule IQGAP-1 [55]. An additional key element also present in the complex is the focal adhesion kinase FAK.…”
Section: Discussionmentioning
confidence: 90%
“…At the same time, via BAD phosphorylation it protects cell from apoptosis, a major cause of tissue damage in reperfusion injury [1,17,21,39,71]. In addition ERK signaling is well known to promote cell survival in different cell types including cardiomyocytes [44,55,59]. The MEK/ERK cascade: from signaling specificity to diverse functions [64].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3A). 37 Interestingly, in vivo analysis on transgenic mice subjected to surgical banding of the aorta demonstrated that melusinbound ERK1/2 is activated following biomechanical stress in a FAK-and MEK1/2-dependent manner (Fig. 3B).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 97%